Strategies for Sustainable Livestock Production in Rural India - Dongre, V. B. (Indian Farming, 2015)
There is a rich biodiversity among the indigenous livestock population of the country to explore it potential, there is need to have panned breeding. Artificial insemination is the key component of livestock improvement. Indigenous breed dilution is now a major challenge ahead of national bureau of animal genetic resources (NBAGR) of India. To overcome this, artificial insemination network at field level should be under the direct control of animal breeder for scientific mating. The effort should be made for promotion to convert the existing stationery government AI centres into mobiles centres for farmer’s doorstep service. The quality of semen stations should follow as per minimum standard of protocol and should be strengthened through induction of quality breeding bulls, upgrading and modernizing semen processing facilities, creating quality control facilities and creating physical infrastructure facilities at semen stations. Inadequate marketing and processing infrastructure facilities to the livestock products makes the livestock sector handicapped and primary producers do not get remunerative prices for their livestock products. The INAPH computer software has a potential to become animal database for the country in near future for animal performance recording at field level, its promotion throughout the country is required.